Differential Expression of Urinary Exosomal MicroRNAs miR-21-5p and miR-30b-5p in Individuals with Diabetic Kidney Disease - Zang, Jinnan (Sci Rep, 2019)
Biomarkers for the identification of diabetic kidney disease (DKD) are needed as current tests lack sensitivity for detecting early kidney damage. MicroRNAs (miRNAs) are short, non-coding regulatory ribonucleic acid (RNA) molecules commonly found in urinary exosomes differentially expressed as renal function declines. We evaluated urinary exosomal miRNA expression in persons with type 2 diabetes mellitus and DKD (T2DKD). 87 human urinary exosomal miRNAs were profiled in a discovery cohort of patients with T2DKD (n = 14) and age and gender matched controls with type 2 diabetes mellitus and normal renal function (T2DNRF; n = 15). Independent validation of differentially expressed target miRNAs was performed in a second cohort with T2DKD (n = 22) and two control groups: T2DNRF (n = 15) and controls with chronic kidney disease (CCKD) and poor renal function without diabetes (n = 18). In the discovery cohort, urinary miR-21-5p, let-7e-5p and miR-23b-3p were significantly upregulated in T2DKD compared to T2DNRF (p < 0.05). Conversely, miR-30b-5p and miR-125b-5p expression was significantly lower in T2DKD (p < 0.05). Independent validation confirmed up-regulation of miR-21-5p in the replication cohort in T2DKD (2.13-fold, p = 0.006) and in CCKD (1.73-fold, p = 0.024). In contrast, miR-30b-5p was downregulated in T2DKD (0.82-fold, p = 0.006) and in CCKD (0.66-fold, p < 0.002). This study identified differential expression of miR-21-5p and miR-30b-5p in individuals with diabetic kidney disease and poor renal function. These miRNAs represent potential biomarkers associated with the pathogenesis of renal dysfunction.